2020
DOI: 10.36911/colostrum.v1i2.688
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN TABLET FE + JUS AVOKAD (Persea Americana Mill) TERHADAP KADAR HEMOGLOBIN IBU HAMIL TRIMESTER II DI PMB SURYANI KECAMATAN MEDAN JOHOR TAHUN 2019

Abstract: Introduction: Anemia is a biggest health in the world. According to WHO the prevalence of anemia in pregnant women was 41,8%. Based on the results of Riskesdas that the proportion of anemia in pregnant women in 2013 was 37,1% and in 2018 of 48,9%. To prevent anemia, pregnant women are expected to get at least 90 iron tablets during pregnancy and consume iron-rich foods. Avocados have the nutrients of vitamin C, vitamin E, vitamin K, iron, folic acid, potassium, calories and fat. Iron in avocados is useful for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…Previous research conducted by Amelia et al (2020) showed that giving avocado juice increased hemoglobin levels. In line with research conducted by Utami et al, (2020), it was shown that giving Fe tablets and avocado significantly increased hemoglobin levels compared to the control group who only consumed Fe tablets. In research conducted by Rianti et al, (2021) regarding the effect of giving honey on the hemoglobin levels of pregnant women in the third trimester in 2021, it was found that honey was effective in increasing the hemoglobin levels of pregnant women in the third trimester.…”
Section: Introductionsupporting
confidence: 84%
“…Previous research conducted by Amelia et al (2020) showed that giving avocado juice increased hemoglobin levels. In line with research conducted by Utami et al, (2020), it was shown that giving Fe tablets and avocado significantly increased hemoglobin levels compared to the control group who only consumed Fe tablets. In research conducted by Rianti et al, (2021) regarding the effect of giving honey on the hemoglobin levels of pregnant women in the third trimester in 2021, it was found that honey was effective in increasing the hemoglobin levels of pregnant women in the third trimester.…”
Section: Introductionsupporting
confidence: 84%
“…The results of this study align with research conducted by Tuju et al (2019), which showed that a combination of 200 g of bananas and 60 mg of iron supplementation for 7 days could signifi cantly increase hemoglobin levels compared to iron supplementation alone. Another study conducted by Utami (2020), also indicates that the combination of 100 g of avocado and 60 mg of iron supplementation for 7 days can result in a higher increase in hemoglobin levels compared to iron supplementation alone. Damayanti et al (2021) also researched the combination of 1 tablespoon of honey and 60 mg of iron supplementation for 14 days, resulting in a higher increase in hemoglobin levels than 60 mg of iron supplementation alone.…”
Section: G I V I N G C a V A S M O O T H I E A N D I R O N Supplement...mentioning
confidence: 94%